1976
DOI: 10.1139/z76-194
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the diet of Myotis lucifugus (Chiroptera: Vespertilionidae)

Abstract: By analysis of feces collected from bats in the field, we determined that aquatic insects, particularly chironomid Diptera, made up the major portion of the diet of Myotis lucifugus at sites in southern Ontario, northern New York, and Nova Scotia. The diets of adult males reflected the available insect prey as sampled by a malaise trap, while those of lactating females included proportionally more caddis flies and moths than were present in the malaise trap samples. The diets of subadults of both sexes showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
116
1
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(128 citation statements)
references
References 0 publications
9
116
1
2
Order By: Relevance
“…These results are quite different from those reported by Funakoshi and Uchida (1981), who found that prey items of this species (described as V. superans superans) in August included Coleoptera (86%), Lepidoptera (5%) and others (9%). Such intraspecies variation in diet composition has been shown in several bat species (Eptesicus nilssonii: Rydell 1986, Vespertilio murinus: Rydell 1992, Eptesicus fuscus: Whitaker 1995b; Agosta and Morton 2003, Pipistrellus abramus: Hirai and Kimura 2004), and these differences might reflect variations in local insect abundance (Belwood and Fenton 1976;Whitaker 1995b). The maternity roost studied by Funakoshi and Uchida (1981) was situated on a small rocky island surrounded by ocean in Fukuoka prefecture (33°40'N, 130°13'E), 1380 km south-west from our study site, and was located in a warm-temperate zone, whereas our study area was located in a cool-temperate zone.…”
Section: Discussionmentioning
confidence: 80%
“…These results are quite different from those reported by Funakoshi and Uchida (1981), who found that prey items of this species (described as V. superans superans) in August included Coleoptera (86%), Lepidoptera (5%) and others (9%). Such intraspecies variation in diet composition has been shown in several bat species (Eptesicus nilssonii: Rydell 1986, Vespertilio murinus: Rydell 1992, Eptesicus fuscus: Whitaker 1995b; Agosta and Morton 2003, Pipistrellus abramus: Hirai and Kimura 2004), and these differences might reflect variations in local insect abundance (Belwood and Fenton 1976;Whitaker 1995b). The maternity roost studied by Funakoshi and Uchida (1981) was situated on a small rocky island surrounded by ocean in Fukuoka prefecture (33°40'N, 130°13'E), 1380 km south-west from our study site, and was located in a warm-temperate zone, whereas our study area was located in a cool-temperate zone.…”
Section: Discussionmentioning
confidence: 80%
“…Specifically, the diet of this species is comprised mostly of the insect orders Diptera, Lepidoptera, Coleoptera, Thrichoptera, Ephemeroptera, and Neuroptera with about the same frequency as these insects are available in the foraging area of bats . In many areas, this bat feeds over open water and at the margins of bodies of water and forests Barclay 1991;Belwood and Fenton 1976;Fenton and Bell 1979;Saunders and Barclay 1992). However, foraging habitats appear to vary depending on intraspecific competition and flight ability.…”
Section: E Foragingmentioning
confidence: 99%
“…认为不同种类的蝙蝠具有 不同的捕食策略及食物资源, 从而尽量避免种间竞 争。鼠耳蝠属有很多形态相类似且常常共栖一地的 种类, 其捕食策略及食物结构却不相同。如大鼠耳 蝠(M. myotis) 和尖耳鼠耳蝠(M. blythii), 这两种形态 非常相似的蝙蝠 (Arlettaz et al, 1991;Ruedi et al, 1990)常常共栖一地, 而食性却大不相同, 前者喜欢 在 地 面 取 食 步 甲 类 昆 虫 , 后 者 则 喜 食 螽 斯 类 (Arlettaz, 1996(Arlettaz, , 1999Arlettaz & Perrin, 1995;Arlettaz et al, 1991Arlettaz et al, , 1993Arlettaz et al, , 1997。 北美长耳鼠耳蝠(M. evotis)和北美鼠耳蝠(M. auriculus)曾长期被误认为 是同一个种 (Genoways & Jones Jr, 1969), 但食性分 析后发现前者的主要食物为夜蛾类, 后者则喜食甲 虫 (Black, 1974)。Begon et al (1996 (Belwood & Fenton, 1976), 然后将粪 便颗粒置于培养皿中, 并在培养皿下部放一细网筛, 在解剖镜下鉴定粪便中的昆虫残骸, 参考郭振中编 著的《贵州农林昆虫志》 (Guo et al, 1987), 主要鉴 定到目, 对鞘翅目鉴定到科; 同时通过网筛观察统 计各类昆虫所占的体积百分比。所有数据用 SPSS 13.0 for Windows 软件进行处理分析。实验数据用 单因素方差分析 (One-way ANOVA), 以 P=0.05 For each parameter, different letters among species is the same as shown in Tab.1. (Faure & Barclay, 1992 [J].…”
Section: 栖一地 这必然会引起对食物和空间资源的竞争。unclassified